A cohort study of factors influencing the physical fitness of preschool children: a decision tree analysis - Wendi Lv; Wendi Lv; Jinmei Fu; Guanggao Zhao; Zihao He; Shunli Sun; Ting Huang; Runze Wang; Delong Chen; Ruiming Chen (Frontiers Media S.A., 2023)
ObjectiveBased on the decision tree model, to explore the key influencing factors of children's physical fitness, rank the key influencing factors, and explain the complex interaction between the influencing factors.MethodsA cohort study design was adopted. 1,276 children (ages 3-6) from 23 kindergartens in Nanchang, China, were chosen for the study to measure the children's physical fitness at baseline and a year later and to compare the physical fitness scores at the two stages. The study was conducted following the Chinese National Physical Fitness Testing Standard (Children Part); To identify the primary influencing factors of changes in physical fitness, a decision tree model was developed, and a questionnaire survey on birth information, feeding patterns, SB, PA, dietary nutrition, sleep, parental factors, and other relevant information was conducted.ResultsThe levels of physical fitness indicators among preschool children showed a significant increase after 1 year. The accuracy of the CHAID model is 84.17%. It showed that 7 variables were strongly correlated with the physical changes of children's fitness, the order of importance of each variable was weekend PA, weekend MVPA, mother's BMI, mother's sports frequency, father's education, mother's education, and school day PA. Three factors are related to PA. Four factors are related to parental circumstances. In addition to the seven important variables mentioned, variables such as breakfast frequency on school day, puffed food, frequency of outing, school day MVPA, parental feeling of sports, father's occupation, and weekend breakfast frequency are all statistically significant leaf node variables.ConclusionPA, especially weekend PA, is the most critical factor in children's physical fitness improvement and the weekend MVPA should be increased to more than 30 min/d based on the improvement of weekend PA. In addition, parental factors and school day PA are also important in making decisions about changes in fitness for children. The mother's efforts to maintain a healthy BMI and engage in regular physical activity are crucial for enhancing the physical fitness of children. Additionally, other parental factors, such as the parents' educational levels and the father's occupation, can indirectly impact the level of physical fitness in children.